Treatment of Liver Metastases in Patients with Neuroendocrine Tumors of Gastroesophageal and Pancreatic Origin - Ping Gu (International Journal of Hepatology, 2012)
Well-to-moderately differentiated neuroendocrine tumors of gastroesophageal and pancreatic origin (GEP-NETs) with liver metastasis are a heterogeneous group of malignancies for which a range of therapeutic options have been employed. Surgical resection of hepatic metastases or hepatic artery embolization may be beneficial in patients with hepatic-predominant metastatic disease. Patients with “carcinoid” syndrome and syndromes associated with functional pancreatic NET (PNET) can be effectively treated with somatostatin analogs. On the other hand, the efficacy of systemic chemotherapy for these patients is limited. A placebo-controlled, double-blind, prospective, and randomized study showed that octreotide LAR improves progression-free survival in patients with advanced midgut functional “carcinoids.” In patients with advanced pancreatic NET, randomized, placebo-controlled studies have recently demonstrated that treatment with the tyrosine kinase inhibitor sunitinib or with mTOR inhibitor everolimus is associated with improved progression-free survival. Based on these studies, octreotide LAR, sunitinib, or everolimus are now considered as first-line therapeutic options in patients with advanced NET. Future studies will likely further define the role of these agents in patients with carcinoid liver metastasis and pancreatic NET liver metastasis.